The Double Crisis of Representation and Participation in Brazil. Issue 3 (3rd July 2019) - Avritzer, Leonardo
ABSTRACT: The Brazilian political system is a mix of representation and participation and innovation and political continuity. It introduced several new form of direct participation but also kept the proportional system with a strong president. The design of the Brazilian system divided political scientists, a few of them arguing the system could not possibly produce governability (Ames, B. 2001. The Deadlock of Democracy in Brazil: Interests, Identities, and Institutions in Comparative Politics . Ann Arbor: University of Michigan Press) whereas others argued that the system could produce good governance and executive branch legislative success (Figueiredo, A. C., & Limongi, F. 2010. Presidential power, legislative organization, and party behavior in Brazil. Comparative Politics, 32 (2), 151–170). In addition to that, the Brazilian institutional design strengthened the Supreme Court and the judicial system as a whole, an act that opened a judicial venue in the process of citizens representation in the process of expansion of rights. In this article, we are going to assume an intermediate position in the debate between Ames and Limongi. We will argue that the system of representation in Brazil was built upon several design problems but could work well as long as it interacted with a system of participation that help to give it legitimacy. In addition to that the political system lost influence to the judicial system in the representation of citizenship. The political arrangement based on the integration of representation and participation was provisional and collapsed after the June 2013 demonstrations opening the way for different attacks on representation and participation by both social actors and the judicial system.